Occurrence of β-Lactamase-Producing Gram-Negative Bacterial Isolates in Water Sources in Cali City, Colombia - Monica Chavez Vivas; Luz Dary Caicedo; Jorge Enrique Castillo (International Journal of Microbiology)
Introduction. Pollution by domestic, industrial, and hospital wastes of the artificial and natural waters of the city of Cali led us to investigate the presence of Gram-negative bacteria resistant to antibiotics in these aquatic ecosystems. Material and methods. We used culture-dependent methods and molecular techniques to investigate the prevalence and dynamics of β-lactamase producing Gram-negative bacteria in five areas located in channels and rivers that cross the city of Cali in January (dry season) and May (wet season). The association between the variables was determined by the chi-square test, using the statistical package SPSS vs 23.0. Results. The main species being Escherichia coli and Pseudomonas spp. with associated resistance to both cefoxitin and cefotaxime were observed in 73.3% isolates during the dry season. Most of the isolates belonged to antibiotype 3 (with resistance to 6 antibiotics), 51.2% in the dry season and 48.9% in the wet season, and they were found especially in the artificial waters of “Intersector Canal (CVC) Sur”. Conclusion. These results indicate that β-lactamase-producing Gram-negative bacteria are widespread in the environment in the aquatic ecosystem of Cali city. The artificial and natural waters that cross the city are finally discharged into the Rio Cauca; this river can then be considered as a medium for the spread of bacterial antibiotic resistance genes.